2012
DOI: 10.1159/000336288
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Levels in the Course of Mild Biliary Pancreatitis

Abstract: Objectives: Obesity markedly increases the risk of severe acute pancreatitis (AP). Several adipokines have been ascribed a role as a predictor of clinical severity in AP. Therefore, the aim of this study was to investigate a possible relationship between leptin and adiponectin and mild biliary AP. Methods: We included 24 consecutive patients with mild biliary AP and 24 consecutive healthy age- and sex-matched controls. Clinical severity was classified by the Ranson score. ELISA was used to assess leptin and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…This was accompanied with improvement of pancreatic histopathological changes which is in agreement with the data of Ghantous et al (2015). This can be explained by inhibition of pancreatic exocrine secretion through direct effect on pancreatic acini with subsequent reduction of intrapancreatic enzyme activity and attenuation of pancreatic damage in the course of AP, increase in the anti-inflammatory mediators with decrease in the release of pro-inflammatory cytokines, glucocorticoids release, decrease in inducible NO and increase in antioxidant level (Demirci et al 2012;Zhou et al 2016).…”
Section: Discussionsupporting
confidence: 81%
“…This was accompanied with improvement of pancreatic histopathological changes which is in agreement with the data of Ghantous et al (2015). This can be explained by inhibition of pancreatic exocrine secretion through direct effect on pancreatic acini with subsequent reduction of intrapancreatic enzyme activity and attenuation of pancreatic damage in the course of AP, increase in the anti-inflammatory mediators with decrease in the release of pro-inflammatory cytokines, glucocorticoids release, decrease in inducible NO and increase in antioxidant level (Demirci et al 2012;Zhou et al 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Hence, it is conceivable that EN exerts its effect via a mechanism other than improvement in gut barrier function, at least in some patients. A possible alternative mechanism for the therapeutic benefit of EN is through adipokines – adipose tissue-derived cytokines ( 19 , 20 ) . A recent clinical study of sixteen patients with Crohn's disease found that patients who received exclusive EN for 4 weeks prior to ileal resection had lower leptin concentrations and higher adiponectin concentrations compared with those who received no specific nutrition therapy ( 21 ) .…”
mentioning
confidence: 99%